Fandom dan Konsumsi Media: Studi Etnografi Kelompok Penggemar Super Junior, ELF Jogja - Ratna Permata Sari (Program Studi Ilmu Komunikasi, 2012)
Korean Wave (music, movie, and drama), recently, accept a lot of attention from Indonesian teenagers. Thanks to the power of mass media, Korean music, or we called it KPop, beginning to spread it virus throughout the world by the emerging of Fandom. Super Junior as one of the pioneer of Korean boy band become the group that has the largest fan club in the world named ELF. This research examines the private media consumption behavior by ELF Jogja and the interaction between its members in organic and virtual community. Ethnographic became the main method by using participant observation, indepth interview, and focus group discussion with snow ball technique. The finding are (1) the private media consumption behavior of fans showed that the fans had